Strategi Umum Porter (Generic Strategic Porters) - Zahra, Sufiani; Affandi, Muh; Awaluddin, Murtiadi; ., Sudirman (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Increasingly complex business competition in the digital era demands that companies, including local MSMEs and startups, develop effective and adaptive competitive strategies. One of the most widely used approaches is Porter's Generic Strategies, which encompass differentiation, cost leadership, and focus strategies. However, the emerging problem is the suboptimal application of Porter's generic strategies in the context of local digital businesses in Indonesia, as well as the limited number of studies examining their suitability to current market dynamics. This study aims to analyze the relevance of Porter's Generic Strategies in facing the challenges of modern competition, particularly in the local digital business sector. The method used is a qualitative approach through library research, with data sources consisting of books, scientific journals, and case studies from local companies. The analytical techniques used are descriptive-critical and thematic analysis. The results show that Porter's Generic Strategies remain relevant as a basic framework for strategy development, but require adaptation to technological changes, digital consumer preferences, and rapid market dynamics. Case studies of startups and MSMEs demonstrate that a combination of strategies—such as technology-based cost leadership and service differentiation—can be an effective solution for building competitive advantage. This study is expected to provide theoretical and practical contributions for academics and business actors in developing appropriate strategies in the digital era.